The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1039/c7nj01311f
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chalcogen substitution on the structure and spectroscopy of 4,7-dimethyl-2H-chromen-2-one/thione analogues

Abstract: The structural and spectroscopic properties of the 1-benzopyran-2-one/thione moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Thionation-induced bathochromic shifts are well-documented for carbonyl-containing chromophores, such as those of coumarin, naphthalene diimide (NDI), and diketopyrrolopyrrole (DPP) dyes. This is a manifestation of the decrease in the energy gap between the occupied and unoccupied frontier orbitals of such chromophores, which occurs when oxygen is replaced by the heavier sulfur. , For the parent dioxobimanes 1 and 2 , density functional theory (DFT) calculations have previously demonstrated that the electronic transitions between those frontier orbitals, which fall within the UV–vis range, are π → π* and n → π*. , Moreover, the lowest energy transitions in these dioxobimanes have been shown to be π → π*, and these are associated with the observed absorption peaks of longest wavelength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thionation-induced bathochromic shifts are well-documented for carbonyl-containing chromophores, such as those of coumarin, naphthalene diimide (NDI), and diketopyrrolopyrrole (DPP) dyes. This is a manifestation of the decrease in the energy gap between the occupied and unoccupied frontier orbitals of such chromophores, which occurs when oxygen is replaced by the heavier sulfur. , For the parent dioxobimanes 1 and 2 , density functional theory (DFT) calculations have previously demonstrated that the electronic transitions between those frontier orbitals, which fall within the UV–vis range, are π → π* and n → π*. , Moreover, the lowest energy transitions in these dioxobimanes have been shown to be π → π*, and these are associated with the observed absorption peaks of longest wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…Thionation-induced bathochromic shifts are well-documented for carbonyl-containing chromophores, such as those of coumarin, 22 naphthalene diimide (NDI), 23 and diketopyrrolopyrrole (DPP) 24 dyes. This is a manifestation of the decrease in the energy gap between the occupied and unoccupied frontier orbitals of such chromophores, which occurs when oxygen is replaced by the heavier sulfur.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we studied the synthetic potential of isochromen-1-ones 3 using them as substrates in thionation reactions. The conventional procedures reported in the literature for the thionation involve refluxing a mixture of the substrate and a large excess of 2,4-bis­(4-methoxyphenyl)-2,4-dithioxo-1,3,2,4-dithiadiphosphetane (the Lawesson’s reagent) in dry toluene or benzene for several hours under inert atmosphere . As mentioned before, our research group has invested in the development of green methods for obtaining organochalcogen compounds.…”
Section: Resultsmentioning
confidence: 99%